Design, manufacture and testing of porous materials with ordered and random porosity: Application to porous medium burners. (25th July 2019) - Samoilenko, Mykhailo; Seers, Patrice; Terriault, Patrick; Brailovski, Vladimir
Highlights: Proposed application of diamond lattice structures in porous burners. Diamond lattices are designed with same porosity and permeability as ceramic foams. 3D additive manufacturing is used to print CoCr structured and unstructured foams. CoCr alloy can be used in two-section porous burner under firing condition. Diamond lattice offered better rigidity than foam under firing condition. Abstract: Digital replicas of three types of SiSiC ceramic foams (10, 30, and 60 pores per inch, PPI) were obtained by means of X-ray computed tomography. Equivalent pore diameters were determined using a combination of the 3D Watershed analysis (VG Studio Max software) and an analytical tetrakaidecahedron model of a cellular structure and compared to those provided by the manufacturer. Upon investigation, it was found that pore diameters provided by the manufacturer were underestimated and the discrepancies between them and the CT-measured values were 10% for 10 PPI, 60% for 30 PPI and 120% for 60 PPI specimens. Next, diamond lattice structures equivalent to 10, 30, and 60 PPI foams in terms of their porosity and permeability were designed and some of them 3D-printed from metallic CoCr alloy. A two-section porous medium burner test bench was then used to measure the temperature, pollutant emissions and pressure drop for six different setups containing, in the upstream and downstream sections, different arrangements of the foam and lattice structures made of either ceramic or metal materials. In all the setups, pollutant emissions were low and at the detection limit of the equipment, which agrees with previous research. The application of CoCr alloy in the upstream section was determined to be advantageous, ensuring higher flame stability and structural strength. The diamond lattice was found to be a good candidate for replacement of the foam geometry by providing both the better control of porosity and higher structural stiffness. Further research with ordered porous materials is recommended for a broad range of lean combustion regimes with metallic alloys in the upstream section, and ceramic materials in the downstream section.